What You Mark is What Apps See - Raval, Nisarg; Srivastava, Animesh; Razeen, Ali; Lebeck, Kiron; Machanavajjhala, Ashwin; Cox, Landon (MobiSys, 2016)
Users are increasingly vulnerable to inadvertently leaking sensitive information through cameras. In this paper, we investigate an approach to mitigating the risk of such inadvertent leaks called privacy markers. Privacy markers give users fine-grained control of what visual information an app can access through a device’s camera. We present two examples of this approach: PrivateEye, which allows a user to mark regions of a two-dimensional surface as safe to release to an app, and WaveOff, which does the same for threedimensional objects. We have integrated both systems with Android’s camera subsystem. Experiments with our prototype show that a Nexus 5 smartphone can deliver near realtime frame rates while protecting secret information, and a 26-person user study elicited positive feedback on our prototype’s speed and ease-of-use.